2005
DOI: 10.4049/jimmunol.174.9.5270
|View full text |Cite
|
Sign up to set email alerts
|

Cellular FLIP (Long Form) Regulates CD8+ T Cell Activation through Caspase-8-Dependent NF-κB Activation

Abstract: Cellular FLIP long form (c-FLIPL) was originally identified as an inhibitor of Fas (CD95/Apo-1). Subsequently, additional functions of c-FLIPL were identified through its association with receptor-interacting protein (RIP)1 and TNFR-associated factor 2 to activate NF-κB, as well as by its association with and activation of caspase-8. T cells from c-FLIPL-transgenic (Tg) mice manifest hyperproliferation upon activation, although it was not clear which of the various functions of c-FLIPL was involved. We have fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 36 publications
5
95
1
Order By: Relevance
“…Similarly, B cells deficient for Fadd or caspase-8 exhibit defects in Tlr3,4-mediated proliferation and mitogen-dependent antibody responses (19)(20)(21). To explain this effect, reports have supported a role for caspase-8 and Fadd in NF B activation (20,(22)(23)(24), whereas other studies show their absence has no effect (18,19,21,25).…”
mentioning
confidence: 72%
“…Similarly, B cells deficient for Fadd or caspase-8 exhibit defects in Tlr3,4-mediated proliferation and mitogen-dependent antibody responses (19)(20)(21). To explain this effect, reports have supported a role for caspase-8 and Fadd in NF B activation (20,(22)(23)(24), whereas other studies show their absence has no effect (18,19,21,25).…”
mentioning
confidence: 72%
“…c-FLIP L , which resembles caspase-8 albeit lacking the proteolytically active cysteine in the caspase homology domain, is able to participate in autoprocessing and membranerestricted activation of caspase-8 (29 -32). c-FLIP L can also be cleaved by caspase-8, and the cleaved p43 form of c-FLIP L has been suggested to promote NF-B signaling (33)(34)(35)(36)(37)(38). In contrast, c-FLIP S , which lacks the caspase homology domain, inhibits binding and oligomerization of caspase-8 in the DISC, thereby preventing the activating cleavage of caspase-8 (29) and generation of the cleaved NF-B-activating fragment of c-FLIP L .…”
Section: Fever-like Hyperthermia Controls T Lymphocyte Persistence Bymentioning
confidence: 99%
“…In further support, c-FLIP L has also been shown to interact with Raf1, a member of the ERK pathway, and with other signaling proteins that activate NF-kB including TNFR-associated factor 1 (TRAF1), TRAF2 and receptor-interacting protein 1 (RIP1). Perhaps more importantly, subsequent effort has demonstrated that proteolytic cleavage of the flexible intersubunit linker within FLIP's protease-like domain (at D376) by procaspase-8 promotes the recruitment of TRAF2 (Kataoka and Tschopp, 2004) and RIP1 (Dohrman et al, 2005) to receptor complexes. Additional evidence also suggests that c-FLIP (both the long and short forms) can be further cleaved at D198 by procaspase-8 to generate a p22 form that only consists of its amino-terminal tandem DEDs, and this form directly interacts with and recruits the regulatory subunit IKKg of the IkB kinase (IKK) complex to potently activate NF-kB (Golks et al, 2006).…”
Section: The Core Disc Components Are Also Involved In Proliferationmentioning
confidence: 99%